Safety of low-dose anticoagulation in extracorporeal membrane oxygenation using the Permanent Life Support System: a retrospective observational study - Kyungsub Song; Jae Bum Kim (Journal of Yeungnam Medical Science, 2023)
Background Bleeding and thrombosis are major complications associated with high mortality in extracorporeal membrane oxygenation (ECMO) management. Anticoagulant therapy should be adequate to reduce thrombosis. However, related studies are limited. Methods We retrospectively reviewed all patients supported with ECMO at a single institution between January 2014 and July 2022 and included those on all types of ECMO using the Permanent Life Support System. Patients were classified into two groups according to their measured mean activated partial thromboplastin time (aPTT) during ECMO management: a high-anticoagulation (AC) group (aPTT, ≥55 seconds; n=52) and a low-AC group (aPTT, <55 seconds; n=79). The primary outcome was thrombotic or bleeding events during ECMO. Results We identified 10 patients with bleeding; significantly more of these patients were in the high-AC group (n=8) than in the low-AC group (15.4% vs. 2.5%, p=0.01). However, thrombus events and oxygenator change-free times were not significantly different between the two groups. Four patients in the high-AC group died of bleeding complications (brain hemorrhage, two; hemopericardium, one; and gastrointestinal bleeding, one). One patient in the low-AC group developed a thrombus and died of ECMO dysfunction due to circuit thrombosis. Conclusion Heparin did not significantly improve thrombotic outcomes. However, maintaining an aPTT of ≥55 seconds was a significant risk factor for bleeding events, especially those associated with mortality.